Surgical Management of Breast Cancer in 2010–2011 SEER Registries by Hormone and HER2 Receptor Status - Lizarraga, Ingrid (Ann Surg Oncol, 2015)
BACKGROUND: Although locoregional recurrence is known to affect overall survival for operable breast cancer, the impact of receptor status on locoregional control is debated. Currently, hormone receptor (HR) and human epidermal growth factor receptor-2 (HER2) status are generally not considered relevant to surgical choice. This study examines recent population-level surgical trends with regard to receptor status. METHODS: We used the Surveillance, Epidemiology, and End Results (SEER) data to identify stage I–III female breast cancers diagnosed from 2010 to 2011. Patients were categorized by HR and HER2 receptor status. Univariate and multivariate logistic regressions were used to assess factors associated with undergoing mastectomy and the choice of contralateral prophylactic mastectomy (CPM). RESULTS: The overall mastectomy rate for the 87,504 women diagnosed in 2010–2011 was 43.4 %. On multivariate analysis, the odds of receiving mastectomy was greater for HER2-positive disease with either HR-negative or HR-positive status, than for women with HER2-negative/HR-positive disease (odds ratio 1.73 and 1. 31, respectively; all p values <0.001). Age, stage, marital status, race, and year of diagnosis also correlated with mastectomy. Triple-negative breast cancer (TNBC) was associated with CPM, while HER2 status was not. The mastectomy rate, which increased overall from 2006 to 2010, has continued to increase for stage III disease but has decreased for stage I disease. Mastectomy rates overall were lower in 2011 than 2010 (p = 0.012). CONCLUSIONS: HER2-positive disease and TNBC were independent predictors of more extensive surgery in this large, recent, population-based cohort. Although mastectomy rates have continued to increase for stage III disease, mastectomy rates overall were lower in 2011 than in previous years.